2014
DOI: 10.1128/jvi.02013-14
|View full text |Cite
|
Sign up to set email alerts
|

High Eomesodermin Expression among CD57 + CD8 + T Cells Identifies a CD8 + T Cell Subset Associated with Viral Control during Chronic Human Immunodeficiency Virus Infection

Abstract: During HIV infection, increased CD57 expression among CD8؉ T cells has been associated with immune senescence and defective immune responses. Interestingly, CD57-expressing CD8؉ T cells exhibit a dual profile, being simultaneously highly cytotoxic (terminally differentiated effectors) and poorly proliferative (replicative senescent). Recent publications point toward a positive role of CD57-expressing CD8 ؉ T cell subsets, presumably due to their high cytolytic activity. We further investigated the phenotype of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
(46 reference statements)
4
21
2
Order By: Relevance
“…We also found that, similarly to what we recently reported for CD8 T cells (24), T-bet upregulation during NK terminal differentiation occurred concomitantly with progressive Eomes downregulation. These results suggest that T-bet and Eomes in cytotoxic lymphocytes are coexpressed in differential gradients that seem to regulate cytotoxic cell effector functions.…”
Section: Discussionsupporting
confidence: 67%
“…We also found that, similarly to what we recently reported for CD8 T cells (24), T-bet upregulation during NK terminal differentiation occurred concomitantly with progressive Eomes downregulation. These results suggest that T-bet and Eomes in cytotoxic lymphocytes are coexpressed in differential gradients that seem to regulate cytotoxic cell effector functions.…”
Section: Discussionsupporting
confidence: 67%
“…Eomes, and the related transcription factor T-bet play partially redundant roles in CD8+ T cells, although Eomes also plays unique roles in the maintenance of memory and exhausted T cells (Banerjee et al, 2010; Intlekofer et al, 2005; Paley et al, 2012). Interestingly, high Eomes expression is also associated with a proliferative subset of CD8+ T cells found in some HIV-infected individuals, and correlates with effective viral control (Simonetta et al, 2014). Moreover, Eomes is highly expressed in intermediate neural progenitor cells, where it is required for the maintenance of the intermediate population and ongoing neurogenesis (Hodge et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the expansion of CD57 + CD8 + T-cells is a hallmark of latent CMV infection (35). The CD57 + CD8 + T-cell subset is functionally heterogeneous, and includes highly cytotoxic T TE cells that express intermediate levels of EOMES, as well as non-cytotoxic EOMES hi T TE cells with high proliferative capacity (36). These above-referenced studies highlight the existence of functional heterogeneity among the CD8 + T-cell memory subsets.…”
Section: Nk-like Cd8+ T-cells In Virus Infection and Immunosenescencementioning
confidence: 99%
“…Furthermore, targeting peripheral blood pro-inflammatory CD28 − T-cells and NK-like CD8 + T-cells by inhibiting CD137 expression may possibly be of relevance to the treatment of bronchiolitis obliterans syndrome (50). In this regard, the percentage of CD57 + CD8 + T-cells is the strongest immunologic predictor of future cutaneous squamous cell carcinoma and was correlated with increasing CD8 + T-cell differentiation (36). As mentioned above, a high percentage of CD57 + CD8 + T cells are NK-like.…”
Section: Nk-like Cd8+ T-cells and Diseasementioning
confidence: 99%